Characteristics of stress-strain foot model before and after subtalar arthroereisis with implants at the treatment of flatfoot (message 2) - Korolkov, Oleksandr; Rakhman, Paviel; Karpinsky, Mykhaylo; Shishka, Igor; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
One of the modern types of flatfoot surgical treatment is subtalar arthroereisis with implant placement in sinus tarsi. There are a lot of kinds of such implants. Objective: to study stress-strain state of the foot bone elements in normal and in cases of its flatfoot deformity before and after implant placement. Methods: we made finite element model which consist of tibia, fibula, talus, calcaneus, navicular and cuneiform bones. Joint surfaces were modeled with mechanical properties of cartilage tissue. We compared two types of models-conical and cylinder, also made assessment of mechanical properties (titanium, sapphire, carbon) on stress-strain state. Results: using of implants with conical and cylinder shape led to increasing of stress values in the place of contact with the bone, especially on the subtalar surface 8,0 и 7,1 МPа. Difference in stress values on the all areas of the foot model with both implants is not significant, but at cylinder shape implantation we observed quantitatively better indexes improvement. Implant material does not influence on the strain distribution in the foot bones. Conclusions: using of implants for subtalar arthroereisis can influence positively on strain distribution of the foot at its surgical correction. Subtalar arthroereisis is one of the kinds for flatfoot deformity treatment and ankle joint stabilization.